An Irish Union! - (:unkn) unknown (My University, 1801)
Scholarly notes may be added at a later date.
If there be no great love in the beginning. - Yet heaven may decrease it upon better acqua[i]ntance.
1 print : b&w
Keywords: Caricatures; Cartoons; Ireland -- History -- Union, 1801; Shakespeare, William, 1564-1616 -- Merry wives of Windsor.